Exiguobacterium acetylicum transformed poultry feathers into amino acids through an extracellular secretion of keratinolytic enzymes - Tutuka Dlume; Nonso E. Nnolim; Uchechukwu U. Nwodo (AIMS Bioengineering)
The transition from a traditional linear economy to a circular model aims to create a more sustainable future by reducing the adverse effects of agro-waste on the environment. The present study evaluated the metabolic diversity of bacterial isolates from municipal dumpsites for keratinase production and poultry feather valorization. The bacterium with the highest keratinolytic activity was identified through 16S ribosomal ribonucleic acid (rRNA) gene sequencing. The exo-keratinase production by the bacterium was optimized, and the feather hydrolysate obtained from the fermentation process was analyzed for amino acids. Among the twelve bacteria isolated from the dumpsite's sample, three showed significant feather degradation and keratinase production of 89% (744.5 ± 9.19 U/mL), 58% (269 ± 15.55 U/mL), and 46% (195 ± 7.07 U/mL) for SSB-03, SSB-02, and HSB-02, respectively. Analysis of the 16S rRNA gene sequence revealed that SSB-03 has high sequence homology with Exiguobacterium acetylicum, and thus, it was identified as Exiguobacterium acetylicum FHBD (accession number MW165834). Strain FHBD fermentation medium exhibited the maximum keratinase activity (2934.54 ± 38.56 U/mL) and sulfhydryl group content (3.09 ± 0.02 mM) at 72 h under optimal process conditions of pH 5.0, temperature (35 °C), inoculum size (2% v/v), and feather (15 g/L). Amino acid analysis of the feather hydrolysate showed significant levels of glutamic acid, aspartic acid, glycine, arginine, serine, and proline, with respective concentrations of 1.58, 1.34, 1.29, 1.20, 1.12, and 0.93 (g/100 g of sample). The study's findings emphasize the potential of E. acetylicum FHBD in poultry feather valorization and keratinase production.